Blood Pressure Profile in School Children (6–16 Years) of Southern India: A Prospective Observational Study - Sayeemuddin, Mohammad; Sharma, Deepak; Pandita, Aakash; Sultana, Tabassum; Shastri, Sweta (Frontiers in Pediatrics, 2015)
Aims and objective: To determine normal blood pressure in apparently healthy, asymptomatic school children in the age group of 6 – 16yrs and to determine the correlation of blood pressure values with different sex, weight, height and Body mass index (BMI) and also to find out prevalence of hypertension in school going population. Material and method: This prospective, observational study enrolled 3302 urban children (1,658boys and 1,644 girls) in the age group of 6-16 years .These were analysed to study the distribution pattern of systolic blood pressure (SBP) and diastolic blood pressure (DBP) at different ages, sex, weight, height and BMI. The systolic and diastolic BP were noted as per age and sex. The association was seen between mean SBP and mean DBP with weight, height and BMI. Information was collected about the family history of hypertension and was correlated with the obtained SBP and DBP readings. Results: The mean systolic blood pressure in males at 6 years was 99.69 ± 3.62 mm of Hg, at 10 years was 102.20 ± 2.16 mm of Hg and at 16 years was 115.33 ± 1.26 mm of Hg. The mean SBP in females at 6 years was 96.55 ± 2.86 mm of Hg, at 10 years was 101.16± 2.12 mm of Hg and at 16 years was 112.41 ± 1.06 mm of Hg. The correlation coefficient for relationship between age and SBP in males and females was 0.89 and 0.91 respectively and for DBP was 0.92 and 0.90 respectively. The correlation coefficient for relationship between height and SBP in males and females was 0.91 and 0.93 respectively and for DBP was 0.92 and 0.88 respectively.The correlation coefficient for relationship between weight and SBP in males and females was 0.92 and 0.92 respectively and for DBP was 0.94 and 0.91 respectively .In the normogram obtained in the study 95%of study population fall between mean +2SD and– 2SD. Conclusion: The Blood pressure (SBP and DBP) tends to increase with age, weight, height and BMI. The Blood Pressure values (SBP and DBP) increases grossly after 11 years of age